Numerical model for composite patch repair of notched aluminum plates under impact loading. (May 2021) - Caliskan, Umut; Ekici, Recep; Yildiz Bayazit, Ayse; Apalak, M Kemal
The damaged area for various structures can be effectively repaired using composite materials. With the effect of impact, damage can occur that cannot be clearly seen in the inner structure of a laminated composite. This can cause delamination and other damage modes in layered composite structures. In this study, three-dimensional dynamic progressive damage analysis was performed in adhesively bonded composite patch-repaired metal notched plates under impact loads to investigate the effect of external composite patch material and thickness. Three-dimensional Hashin damage models were used for the progressive damage model. A user-defined subroutine, VUMAT was written to transfer the damage models to finite element code. By writing a separate script in Python language that relates to the damage models, the weakness in the laminate of the composite patch was transferred to the finite element model with a different degradation model proposed. It was found that plastic deformations occurring after impact damage in the notched metal plates was prevented by the use of composite patches. While glass and carbon fiber exhibit similar behavior at lower impact velocities, the progress of damage is prevented by increasing patch thickness. These behaviors were confirmed by the numerical model and showed an advanced agreement with experimental results.